Azide Quenching of Singlet Oxygen in Suspensions of Microenvironments of Neutral and Surface Charged Liposomes and Micelles. (30th August 2012) - Musbat, Lihi; Weitman, Hana; Ehrenberg, Benjamin
Abstract The azide anion is often used as a physical quencher of singlet oxygen, the important active intermediate in photosensitized oxidation. An observed effect of azide on the rate of a reaction is considered an indication to the involvement of singlet oxygen. In most biological photosensitizations, the light‐absorbing sensitizer is located in a membrane or in an intracellular organelle, whereas azide is water soluble. The quenching it causes relies on a physical encounter with singlet oxygen during the latter's short lifetime. This can happen either if azide penetrates into the membrane's lipid phase or if singlet oxygen is intercepted when diffusing in the aqueous phase. We demonstrate in this article the difference, in liposomes' suspension, between the effect of azide when using a water‐soluble and membrane‐bound chemical targets of singlet oxygen, whereas this difference does not exist when micelles are used. We explain the difference on the population of sensitizer and target in the liposome vs micelle. We also show the effect that exists on azide quenching of singlet oxygen by electrically charged lipids in liposomes. This is a result of the accumulation or dilution of azide in the debye layer near the membranes' surface, due to the surface Gouy–Chapman potential.